Optimized layer architecture for an extended fatigue life of ultrafine-grained AA1050/AA5005 laminated metal composites - Kümmel, Frank; Tegtmeier, Thea-Simone; Höppel, Heinz Werner; Göken, Mathias (IOP Conference Series: Materials Science and Engineering, 2017)
The influence of interfaces on the fatigue life in AA1050/AA5005 ultrafine-grained laminated metal composites was investigated. At constant sheet thickness, the layer thickness and the number of material interfaces was varied by performing different cycles of accumulative roll bonding. It is found that crack deviation occurs if the crack approaches the soft to hard (AA1050/AA5005) material interface resulting in strongly enhanced fatigue lives compared to the mono-material. The most favourable layer architecture for enhanced fatigue life strongly depends on the applied stress amplitudes. At intermediate stress amplitudes a large layer thickness of 500 extgreekmm (N4) and 8 material interfaces gives the longest fatigue life. In contrast, at low stress amplitudes the sheets with 32 material interfaces and a layer thickness of 125 extgreekmm (N6) shows the longest fatigue life.
EAM Import::2019-03-08